2012
DOI: 10.5603/fhc.2011.0088
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between Th17 and regulatory T-cells in systemic lupus erythematosus

Abstract: Impaired function of regulatory T-cells (Treg) leads to a failure in immune tolerance and triggers autoimmunity. We analyzed whether the deficiency in Treg in systemic lupus erythematosus (SLE) is accompanied by an increase in effector T-cell responses. We studied the frequencies of IL-17A (Th17) and IFNg (Th1) producing CD4 + T-cells by flow cytometric detection of intracellular cytokines in PMA/ionomycin stimulated blood lymphocytes from seven patients with active SLE, eight with SLE in remission, and 11 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 30 publications
6
52
0
4
Order By: Relevance
“…In SLE this phenomenon may be associated with impaired immunosuppression, due to persistently lower numbers of regulatory T-cells or their impaired function [36,37]. Similarly to previous report [38], we observed lower frequency of naïve CD4+ T-cells and increased percentage of T EM fraction in both active-and inactive-LN.…”
Section: Discussionsupporting
confidence: 66%
“…In SLE this phenomenon may be associated with impaired immunosuppression, due to persistently lower numbers of regulatory T-cells or their impaired function [36,37]. Similarly to previous report [38], we observed lower frequency of naïve CD4+ T-cells and increased percentage of T EM fraction in both active-and inactive-LN.…”
Section: Discussionsupporting
confidence: 66%
“…TH17 cells secrete a profile of potent proinflammatory cytokines, including IL-17, IL-21, IL-22 and potent TNF-a and IL-6 upon certain stimulation [11]. Recent studies indicated that IL-17 aids in coordinating tissue inflammation [10][11][12]. It has been hypothesized that TH17-cells, in particular, play a pivotal role in the initiation and development of autoimmunity.…”
Section: Introductionmentioning
confidence: 98%
“…At present, human Treg cells can be characterized by a CD4 + CD25 + and transcription factor forkhead box P3 (FoxP3+) phenotype (CD4 + CD25 + FoxP3+). A decreased frequency and/or an impaired function of these cells might be involved in the development of autoimmune diseases [10,14]. Though the concept of the preventive role of Treg cells in autoimmunity is widely accepted, data regarding SLE are inconsistent [10,15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Systemic lupus erythematosus (SLE) is a prototypic systemic autoimmune disease characterized by high levels of serum autoantibodies against different components of cells, leading to systemic tissue and organ damage [1]. However, the aetiology and pathogenic processes of SLE are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%